The effect of Stichopus chloronotus aqueous extract on human osteoarthritis articular chondrocytes in three-dimensional collagen type I hydrogel in vitro - Mohd Heikal Mohd Yunus,; Ahmad Nazrun Shuid,; Mohd Fauzi Busra,; Chua, Kien Hui; Norzana Abdul Ghafar,; Rizal Abd Rani, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Autologous chondrocyte-seeded scaffolds have proved to be one of the most promising alternative therapies for articular cartilage defects. However, the chondrocytes have specific nutritional requirements and risk of dedifferentiation during in vitro expansion. Stichopus chloronotus aqueous extract (SCAE) was investigated as a medium supplement for three-dimensional (3D) collagen type I hydrogel scaffold seeded with chondrocytes to determine whether SCAE is capable of maintaining phenotype and sustaining extracellular matrix synthesis and deposition. Human osteoarthritis articular chondrocytes were isolated from the knee joint cartilage of patients underwent total knee replacement surgery. Human osteoarthritis articular chondrocytes were encapsulated in collagen type I hydrogel and cultured in basic medium with 0, 0.1 and 0.2% of SCAE. The chondrocytes in 3D culture were evaluated by means cell morphology and proliferation, quantitative phenotypic expression of collagen type I, II, aggrecan core protein and sox-9. H&E, toluidine blue staining and sulfated glycosaminoglycan (sGAG) production were analyzed after 7 days in culture. Chondrocytes cultured in 3D with various SCAE concentration appeared with polygonal morphology maintaining their chondrocytes characteristic. SCAE supplementation promoted chondrocytes proliferation and the ability of the cells to express gene encoding collagen type I decreased, whereas their ability to express collagen type II, aggrecan core protein and sox9 increased as compared to control. The cartilaginous matrices were positively stained toluidine blue concomitant with higher sGAG accumulation in SCAE-supplemented culture medium. This study shown that SCAE may be beneficial for in vitro development of 3D chondrocytes culture for use in cartilage tissue engineering therapies.